Aghi Ghayo Onam: Religious and Costumery Tradition by Malay Kampar People in Islamic Perspective - Suroyo, Suroyo; Soedjiwo, Novena Ade Fredyarini; Entas, Derinta; Putra, Bima Maulana (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The festival of Aghi Ghayo Onam (The Sixth Feast Day) is celebrated extensively in Kampar, even more so than Idul Fitri on the first day of Shawwal. This sixth-day celebration has become a customary tradition passed down through generations and regularly practised by the people of Kampar Regency. Previous research lacks a detailed examination of the religious customs and attire of the Malay Kampar Riau community from an Islamic viewpoint. This present study seeks to examine these traditions through an Islamic lens. The research methodology employed was qualitative, with observation of cultural events and practices, and analysis of relevant literature as primary data collection and the support data will involve unstructured interviews with community members. The findings of the study reveal that the Malay Kampar people's Aghi Ghayo Onam tradition is deeply intertwined with their cultural practices. Islamic teachings inform their daily lives, including their clothing, food, and social interactions in the tradition. The community also places great importance on maintaining its cultural identity through its traditional food, which is characterized by vibrant colours, intricate patterns, and the spices of the authentic local food. The study concludes that an understanding of these traditions is essential for promoting interfaith dialogue and cultural understanding in a diverse society.